2009
DOI: 10.1159/000218366
|View full text |Cite
|
Sign up to set email alerts
|

Color Discrimination Performance in Patients with Alzheimer’s Disease

Abstract: Background/Aims: Visual deficits are frequent in Alzheimer’s disease (AD), yet little is known about the nature of these disturbances. The aim of the present study was to investigate color discrimination in patients with AD to determine whether impairment of this visual function is a cognitive or perceptive/sensory disturbance. Methods: A cross-sectional clinical study was conducted in a specialized dementia unit on 20 patients with mild/moderate AD and 21 age-matched normal controls. Color discrimination was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 47 publications
2
43
1
2
Order By: Relevance
“…The findings of the present study come to agreement with Salamone et al (2009), who described that visual disturbances in Alzheimer's disease patients are not due to global cognitive decline but dependent on the damage caused to the primary visual cortex.…”
Section: Discussionsupporting
confidence: 93%
“…The findings of the present study come to agreement with Salamone et al (2009), who described that visual disturbances in Alzheimer's disease patients are not due to global cognitive decline but dependent on the damage caused to the primary visual cortex.…”
Section: Discussionsupporting
confidence: 93%
“…Dementia is linked to hearing impairment and some recent work appears to show that hearing impairment can substantially increase the risk of incident dementia (Lin et al, 2011). Not surprising, visual sensory impairments were also linked with dementia (Adlington, Laws, & Gale, 2009;Salamone et al, 2009), with a possible impact on selective attention performance (Tewari, Shakuf, & van Lieshout, 2014).…”
Section: Intellectual Functions (B117)mentioning
confidence: 99%
“…They also found a significant association between motion threshold and disease severity. However, while some studies have found impairment of detection of motion [11] and impairment of low spatial frequencies [10], many studies have found other visual deficits, including impairment of color (blue-yellow), backward masking, and contrast sensitivity at all frequencies, which cannot be explained by the broad-band pathway deficit [59,60,[68][69][70]. This suggests that it is not only the broad-band pathway which is affected by AD, although it may be a contributory factor in the visual deficits seen in AD.…”
Section: Neuropsychological Studiesmentioning
confidence: 99%